(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study examines the difficulties Uzbek learners face in developing English speaking skills due to differences in syntactic word order. Uzbek follows a Subject–Object–Verb (SOV) structure, while English uses a Subject–Verb–Object (SVO) pattern. These structural differences often cause word order errors, hesitation, and reduced fluency in spoken English. Findings indicate that learners frequently transfer Uzbek syntax into English and experience cognitive load when reorganizing sentences during speech. Two teaching methods—contrastive syntax awareness activities and structured speaking tasks—were identified as effective strategies to help learners internalize English word order and improve fluency.